Risk of systemic allergic reactions to allergen immunotherapy in a pediatric allergy clinic in Turkey. (May 2016) - Bahceci Erdem, Semiha; Nacaroglu, Hikmet Tekin; Karaman, Sait; Unsal Karkıner, Canan Sule; Gunay, Ilker; Dogan, Done; Asilsoy, Suna; Altınoz, Serdar; Can, Demet
Abstract: Objectıves: Even though allergen immunotherapy is an effective treatment method that has been used on rhinitis, asthma and venom anaphylaxis for over 100 years, systemic reactions (SRs) limit the use of this treatment method. We classified SRs associated with subcutaneous immunotherapy (SCIT) according to the World Allergy Organization Subcutaneous Immunotherapy Systemic Reaction Grading System. Risk factors for the SRs were assessed. Methods: In this study 67, 758 injections to 1350 children with allergic rhinitis and/or asthma were analyzed throughout January 1999–December 2014. Results: A total of 51 systemic reactions were observed in 39 patients (0.075% per injection, %3 per patient). Mean age of SRs observed patients was 13 ± 2.6 years (range 9.5–16 years) and 64.1% were male, 35.9% were female. 51.3% of SRs were grade 1, 38.5% grade 2, 7.7% grade 3 and 2.6% grade 4. SRs were early onset in 41% of the patients and delayed onset in 59%. 76.9% of SRs were seen during maintenance therapy and 56.4% during peak pollen season. In 28.2% of cases previous local reactions and in 30.8% previous grade 1 reactions were determined. There was no fatal outcome from any of the SRs. Conclusion: SCIT related SRs are generally of mild severity. Although only 10% of the SRs were grade 3 or 4, there is a still a small risk of severe reactions. 76.9% of SRs were observed during maintenance therapy. Delayed-onset SRs rate in our study is 59%. So both clinicians and parents should be alert about the delayed reactions after SCIT.